Ancient Eco-Theology of Resting the Land: Between Indigenous Ecological Knowledge and Postcolonial Legacies in Indonesia - Mario Christian (LPPM STT Baptis Kalvari, 2026)
This article presents a postcolonial eco-theological study at the intersection of biblical hermeneutics, Ancient Near Eastern (ANE) literature, colonial history, and indigenous ecological knowledge in Indonesia. Rooted in the Levitical concept of land Sabbath and Jubilee (Leviticus 25), the study situates this tradition within a broader ANE framework of periodic land and debt restitution to establish land rest as a trans-cultural, ancient ecological wisdom rather than a narrow religious directive. Drawing on postcolonial analysis of Dutch-colonized Indonesia, the research examines how distinct colonial land governance regimes as the domein verklaring principle converged in their ecological disruption and suppression of indigenous ecological knowledge. The indigenous cosmological frameworks of Dayak communities in Indonesia which encode reciprocal and relational obligations towards land are examined in light of biblical-ANE tradition. The study also employs methodology of grounded postcolonial theological hermeneutics and archival colonial legal analysis. These findings contribute a constructive and decolonized eco-theological framework for land justice advocacy in postcolonial Indonesia, by positioning ancient land rest wisdom as a generative resource for contemporary environmental governance and indigenous rights advocacy.